Protocadherin PAPC is expressed in the CNC and can compensate for the loss of PCNS. Issue 2 (13th January 2014) - Schneider, Martina; Huang, Chaolie; Becker, Sarah F.S.; Gradl, Dietmar; Wedlich, Doris
Summary Protocadherins represent the biggest subgroup within the cadherin superfamily of transmembrane glycoproteins. In contrast to classical type I cadherins, protocadherins in general exhibit only moderate adhesive activity. During embryogenesis, they are involved in cell signaling and regulate diverse morphogenetic processes, including morphogenetic movements during gastrulation and neural crest migration. The two protocadherins paraxial protocadherin (PAPC) and axial protocadherin (AXPC) are indispensable for proper gastrulation movements in Xenopus and zebrafish. The closest relative PCNS instead, is required for neural crest and somite formation. Here, we show that cranial neural crest (CNC) cells in addition to PCNS express PAPC, but not AXPC. Overexpression of PAPC resulted in comparable migration defects as knockdown of PCNS. Moreover, reconstitution experiments revealed that PAPC is able to replace PCNS in CNC cells, indicating that both protocadherins can regulate CNC migration. genesis 00:1–7. © 2013 Wiley Periodicals, Inc.